Study on The Design of Solar-Wind Energy System to Reduce The Use of Gas Fuel in The Southeast Sumatra Block - Eko Adi Nugroho; Suhanan Suhanan; Rochim Bakti Cahyono (Journal of Social Science, 2022)
The Southeast Sumatra block produces oil and gas. Natural gas production of 15,300 MSCF is used as fuel for turbine generators to generate 38 MW of electrical energy, while the rest is used as business products. The application of the solar-wind system can reduce the load on the turbine generator so that gas fuel consumption is also reduced. Five platforms have areas that can be utilized for a solar-wind system. This study aims to determine the amount of gas fuel consumption that can be reduced by the solar-wind system application. The method is simulation using the HOMER software to determine the amount of electrical energy that can be supplied and the costs required by the solar-wind system. The components used are found in the HOMER software and on the market. The simulation results show that the off-grid solar-wind system can provide electricity supply of 50,235 kWh per year and reduce gas fuel consumption by 20,094 MSCF per year. The on-grid solar-wind system can provide electricity supply of up to 81,230 kWh per year and reducing the use of gas fuel by 32,492 MSCF per year. The off-grid solar-wind system will increase gas sales by $132,620 per year with NPV>0 and ROI 21%, while the on-grid system will increase gas sales by $214,447 per year with NPV>0 and ROI 57%. Both models of solar-wind systems have positive economic values ??so that they are feasible to implement